2016
DOI: 10.1037/a0040294
|View full text |Cite
|
Sign up to set email alerts
|

Linear and U-shape trends in the development of expressive drawing from preschoolers to normative and artistic adults.

Abstract: This study sought to explain the apparently conflicting age-incremental and U-shaped developmental patterns found for the merit of expressive drawing by examining the role of representational realism drawing ability in the observed age patterns. Thirty children in each of seven age groups from young children to preadolescence (4, 5, 6, 7, 9, 11 and 12 years) were randomly sampled. Two further groups (normative and artist) of 14-year-olds and young adults were included to assess expressive drawing shown late in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Several commentators have suggested that the -shape curve is dependent upon rating criteria and judges that favor a modernist perspective on art that emphasize expressive formal properties above representation (Duncum, 1986; Jolley, 2010; Pariser, Kindler, & van den Berg, 2008). Indeed, in a recent empirical study seeking to explain these apparently conflicting patterns, Jolley, Barlow, Rotenberg, and Cox (2016) found that age-incremental patterns of expressive drawing measures were observed without statistically controlling for variations in children’s and adults’ representational drawing ability (independently assessed), but patterns tending toward a U-shape curve were found with the statistical control.…”
Section: Development Of Representational and Expressive Drawingmentioning
confidence: 99%
“…Several commentators have suggested that the -shape curve is dependent upon rating criteria and judges that favor a modernist perspective on art that emphasize expressive formal properties above representation (Duncum, 1986; Jolley, 2010; Pariser, Kindler, & van den Berg, 2008). Indeed, in a recent empirical study seeking to explain these apparently conflicting patterns, Jolley, Barlow, Rotenberg, and Cox (2016) found that age-incremental patterns of expressive drawing measures were observed without statistically controlling for variations in children’s and adults’ representational drawing ability (independently assessed), but patterns tending toward a U-shape curve were found with the statistical control.…”
Section: Development Of Representational and Expressive Drawingmentioning
confidence: 99%
“…Children’s ability to employ the aforementioned graphic cues has been associated with their understanding of the depicted themes (Brechet and Jolley, 2014; Brechet et al, 2009) and their representational drawing skills (Brechet and Jolley, 2014; Jolley, 2010; Jolley et al, 2016). Moreover, the majority of the related studies has shown that this is an age-related ability, since as they get older children are able to incorporate in their drawings a greater number and a larger variety of graphic cues (Bonoti and Misailidi, 2015; Brechet et al, 2009; Ives, 1984; Jolley et al, 2004; Misailidi and Bonoti, 2014; Picard and Gauthier, 2012; Picard et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The attachment style is certainly influencing the emotional dimension of a drawing, but there are other ways to approach it. Whatever the attachment style, children show a growing ability, with age, to express emotions in drawings (Jolley et al, 2016). Another aspect of this perspective concerns the emotional valence of the representation: Does the drawing express positive (joy, happiness) or negative (sadness, fear, anger) emotions?…”
Section: Emotionality In Children's Drawings Of Godsmentioning
confidence: 99%